Inducing Chronic Excitotoxicity in the Mouse Spinal Cord to Investigate Lower Motor Neuron Degeneration - Blizzard, Catherine A.; Lee, K. M.; Dickson, Tracey C. (Frontiers in Neuroscience, 2016)
We report the methodology for the chronic delivery of an excitotoxin to the mouse spinal cord via surgically implanted osmotic mini-pumps. Previous studies have investigated the effect of chronic application of excitotoxins in the rat, however there has been little translation of this model to the mouse. Using mice that express yellow fluorescent protein (YFP), motor neuron and neuromuscular junction alterations can be investigate following targeted, long-term (28 days) exposure to the α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor excitotoxin, kainic acid. By targeting the L3-4 region of the lumbar spinal cord, with insertion of an intrathecal catheter into the subarachnoid space at L5, chronic application of the kainic acid results in slow excitotoxic death in the anterior ventral horn, with a significant (P<0.05) reduction in the number of SMI-32 immunopositive neurons present after 28 days infusion. Use of the Thy1-YFP mice provides unrivalled visualisation of the neuromuscular junction and enables the resultant distal degeneration in skeletal muscle to be observed. Both neuromuscular junction retraction at the gastrocnemius muscle and axonal fragmentation in the sciatic nerve were observed after chronic infusion of kainic acid for 28 days. Lower motor neuron, and distal neuromuscular junction, degeneration are pathological hallmarks of the devastating neurodegenerative disease Amyotrophic Lateral Sclerosis (ALS). This mouse model will be advantageous for increasing our understanding of how the pathophysiological phenomena associated with this disease can lead to lower motor neuron loss and distal pathology, as well as providing a robust in vivo platform to test therapeutic interventions directed at excitotoxic mechanisms.